PENERAPAN METODE INKUIRI BERBASIS AUDIO VISUAL “MUSEUM BALI” DALAM MENUMBUHKAN MOTIVASI DAN KESADARAN SEJARAH - Rulianto ruli (Jurnal Pendidikan dan Kebudayaan Missio, 2021)
This study (1) determine whether the application of inquiry method based on audio visual in Bali museum can foster student motivation to learn, (2) Determine whether the application of inquiry method based on audio visual museum Bali can raise awareness of student history. This research is a classroom action research. This research was conducted in two cycles with the research subjects of all third semester students of the Department of History Education at Mahasaraswati Denpasar University in the 2017-2018 academic year as many as 26 people. The method used in this research is the inquiry method. The results of the discussion show that the learning motivation of students has increased which is indicated by the indicator of student curiosity increasing after being tracked using a motivation questionnaire in the learning process. Meanwhile, if it is calculated into numbers, in the first cycle, 16 students have not yet achieved completeness and 10 students have reached completeness. In the second cycle, there was an increase of 17 students whose score was 90, 3 students got a score of 110 while 6 students got a score of 100, thus it could be said that there had been a significant change in student learning motivation. The aspect of historical awareness refers to the score range (100-120 Very good) (90-99 Good) (80-89 Enough) (70-79 Poor) (60-69 Very poor). The results show that the data analysis of the historical awareness questionnaire test of history learning in the first cycle, there are 13 students who get the lowest score. 1 person gets a score of 77, 1 person gets a score of 78.2 people get a score of 79 and 2 people get a score of 80, 1 student gets a score of 86, 3 students get a score of 88, and 3 students get a score of 89. Based on the scoring guidelines found on the observation sheet, the classification is at a sufficient level. In cycle II, 19 students got a score above 90. 1 person got a score of 112, 3 people got a score of 103. 3 people got a score of 120. Based on the scoring guidelines contained in the observation sheet, the classification is at a very good level.